Studi Laju Penurunan Frekuensi Pada Sistem Kelistrikan Sumatera Bagian Utara Dengan Skema Pelepasan Beban - Retno Aita Diantari; Muhammad Rafsanjani (Sutet, 2019)
PT PLN (PERSERO) is a company engaged in electricity in Indonesia and plays a role in the generation and distribution of electricity to consumers. PLN has quality standards that must be met, one of which is a stable frequency even though the load keeps changing all the time. In electric power systems, the frequency value is an indicator of the balance between active power generated with a total load of active system power and losses. The frequency value will increase if there is an excess generation and conversely the frequency value will decrease if there is a shortage of generation or overload. If there is a disturbance that causes the large capacity generating unit to be release from the systems (trip), in this case the PLTU Pangkalan Susu and PLTU Nagan Raya will cause a decrease in frequency so that the Northern Sumatera interconnection system is disrupted. A large decrease in frequency can lead to failure of generating units in a row so that it can cause total system failure (blackout). To avoid a total system failure (blackout) a load shedding scheme with under frequency relay (UFR) is carried out. This research is done by experimental methods. According to this research, it’s been found that the setting of under frequency relay conducted by PLN UP2B Northern Sumatera is good, in this sense of blocking the system from blackout due to a massive power trip.